Estudio de mejora de la gestión de almacén para incrementar la capacidad de almacenaje de Schroth Corporación Papelera S.A.C. - Pinedo Armijo, Edgar John (2019)
The present research work was carried out with the objetive of improving the warehouse management of the company Schroth Corporación Papelera S.A.C., a study that focused mainly on improving the storage capacity of finished products. The methodology used was explanatory and descriptive and data were taken from the company's records (documentaries and presences). The theoretical framework is focused on previous research projects, which were also conducted and directed towards warehouse management. General information was presented of the company describing the products, key processes, infrastructure, in addition to putting emphasis on the presentation information regarding the warehouse management and its storage capacity. The current warehouse management was analyzed according to the information given by the company, information with which a situational diagnosis was made using in addition to other tools the Ishikawa diagram and the Pareto diagram, concluding That their main problems are the poor layout design, the incorrect use of stored procedures and techniques, the deficient inventory management and the improper purchasing management. After a quantitative and qualitative evaluation of these four alternatives of solution through the methods ranking of factors and the matrix of the decision, it was obtained a conclusion that the two main problems that influence the capacity of storage are the Poor layout design and improper use of stored procedures and techniques. To the problems found, proposals for solutions were presented, such as a new layout design and the implementation of a new storage system using selective racks for the relocation of the most profitable products for the company; In addition to the proper use of stored procedures and techniques that specifically complement the use of selective racks. As a result of implementing these improvements, an increase in the storage capacity of the finished product was obtained in 325 Ton., in addition the time of dispatch was reduced, for this it was taken as example a standard operation going from 16,80 minutes to 1,19 minutes; then also recovered areas within each warehouse which together amount to 200 m² which are used as loading and unloading zones in each of the respective warehouses finished product, also managed to move from a chaotic warehouse to a warehouse Order that will allow you to optimize resources. Finally, the financial analysis of the proposals for improvement was carried out, three possible scenarios were presented, negative, conservative and positive, taking as reference the cost of labor, the cost of overtime, the cost of detriment and the Savings in recovered areas. The conditions for the financial economic evaluation of the proposed improvements, in its three scenarios, were the cost of capital which is 18,59%, the period of return of the investment of 18 months; the project will be fully financed by the shareholder and the Investment amounts to S/ 599 867,50. The VNA and the TIR the negative scenario is of S/-137 026,07 and 14% respectively, then for the conservative scenario was obtained a VNA of S/ 34 642,99 and a TIR of 20% and finally par the positive scenario was obtained a VNA of S/ 188 535,23 and a TIR of 25%. This shows that the proposals for improvements are viable in the conservative and positive scenarios.